Influence of diphenyl diselenide on chlorpyrifos-induced toxicity in Drosophila melanogaster (2015)
Exposure to chlorpyrifos (CPF) poses several harmful effects to human and animal health. The present study investigated the influence of diphenyl diselenide (DPDS) on CPF-induced toxicity in Drosophila melanogaster. Firstly, the cumulative responses of virgin flies (2- to 3-day-old) to CPF (0.075–0.6 µg/g) and DPDP (5–40 µmol/kg) in the diet for 28 consecutive days were investigated. Subsequently, the protective effect of DPDS (10, 20 and 40 µmol/kg) on CPF (0.15 µg/g)-induced mortality, locomotor deficits, neurotoxicity and oxidative stress was assessed in a co-exposure paradigm for 7 days. Results showed that CPF exposure significantly decreased the operant reflex in a time- and concentration-dependent manner, whereas the percent live flies with DPDS treatment was not statistically different from control following 28 days of treatment. In the co-exposure study, CPF significantly increased mortality while the survivors exhibited significant locomotor deficits with decreased acetylcholinesterase (AChE) activity. Dietary supplementation with DPDS was associated with marked decrease in mortality, improvement in locomotor activity and restoration of AChE activity in CPF-exposed flies. Moreover, CPF exposure significantly decreased catalase and glutathione-S-transferase activities, total thiol level with concomitant significant elevation in levels of reactive oxygen species and thiobarbituric acid reactive substances in the head and body regions of the treated flies. Dietary supplementation with DPDS significantly improved the antioxidant status and prevented CPF-induced oxidative stress, thus demonstrating the protective effect of DPDS in CPF-treated flies.